2018
DOI: 10.1021/acs.inorgchem.8b01549
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Magnetocaloric Effect in Low Applied Magnetic Fields in LnOHCO3 Frameworks

Abstract: This study probes the structure and magnetocaloric effect of the LnOHCO3 (Ln = Gd3+, Tb3+, Dy3+, Ho3+, and Er3+) frameworks. The combination of single crystal X-ray and neutron powder diffraction indicates that these materials solely adopt the P212121 structure under these synthetic conditions and magnetic susceptibility measurements indicate they remain paramagnetic down to 2 K. We show that the magnetocaloric effects of TbOHCO3 and DyOHCO3 have peak entropy changes of 30.99 and 33.34 J kg–1 K–1 for a 2–0 T f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 40 publications
4
65
0
Order By: Relevance
“…The emergence of short range correlations in only these materials is an important result, as these materials show magnetocaloric properties maximised for use above 4 K for low applied magnetic field changes. 7 Only ErODCO 3 , whose magnetocaloric properties gradually increases on cooling down to 2 K and resembles GdOHCO 3 but with overall poorer performance, did not show any sign of magnetic diffuse scattering, indicating a lack of significant magnetic correlations. It was noted that the strength of magnetic diffuse scattering observed at 1.5 K decreased significantly from TbODCO 3 to HoODCO 3 to DyODCO 3 , indicating a decrease in the strength of the magnetic correlations giving rise to this, but does not correlate with bond distances.…”
Section: Short Range Order In Lnodcomentioning
confidence: 92%
See 3 more Smart Citations
“…The emergence of short range correlations in only these materials is an important result, as these materials show magnetocaloric properties maximised for use above 4 K for low applied magnetic field changes. 7 Only ErODCO 3 , whose magnetocaloric properties gradually increases on cooling down to 2 K and resembles GdOHCO 3 but with overall poorer performance, did not show any sign of magnetic diffuse scattering, indicating a lack of significant magnetic correlations. It was noted that the strength of magnetic diffuse scattering observed at 1.5 K decreased significantly from TbODCO 3 to HoODCO 3 to DyODCO 3 , indicating a decrease in the strength of the magnetic correlations giving rise to this, but does not correlate with bond distances.…”
Section: Short Range Order In Lnodcomentioning
confidence: 92%
“…It has previously been reported that the LnOHCO 3 frameworks do not show any indication of long range order down to 2 K, and follow Curie-Weiss behaviour, with Weiss temperatures of À5.04 K, À0.84 K, À3.83 K and À7.47 K, for Tb, Dy, Ho and Er. 7 Magnetic susceptibility measurements below 2 K of TbOHCO 3 and HoOHCO 3 show features indicative of the formation of long range order (Fig. 2) at B1.2 K and B0.8 K, respectively.…”
Section: Physical Property Measurementsmentioning
confidence: 93%
See 2 more Smart Citations
“…[7] Recently however, magnetic studies of MOFs have emerged, highlighting the potential of magnetic metal-organic frameworks in functional magnetic materials. MOFs have already been shown to exhibit a range of magnetic properties, with uses in chemical and magnetic sensors, [8] magnetocalorics [9,10] and multiferroics that combine magnetism with ferroelectric order. [11] The ability for greater flexibility in the design of MOFs, allows for more specific topologies and magnetically isolated sheets and chains, opening up the means to low dimensional and frustrated magnetism.…”
Section: Introductionmentioning
confidence: 99%